2013
DOI: 10.1002/sce.21081
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Pedagogical Content Knowledge of Scientific Argumentation: The Impact of Professional Development on K-12 Teachers

Abstract: One of the hallmarks of science and science education is the production of new knowledge about the natural world through objective argument and critique. Teachers’ understanding of scientific argumentation impacts how they incorporate this important scientific practice into science classrooms. This study examined how three professional development workshop series grounded in authentic practice impacted 70 elementary, middle, and high school teachers’ pedagogical content knowledge (PCK) for scientific argumenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 60 publications
(157 reference statements)
4
103
0
24
Order By: Relevance
“…Considering the current literature, much work remains in developing valid and reliable assessments of argumentation-particularly oral argumentation, as McNeill and Knight (2013) found that many teachers reported difficulty making sense of the quality of oral arguments during classroom discussions. Hence the need for more attempts to develop assessments of oral argumentation.…”
Section: Moving Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the current literature, much work remains in developing valid and reliable assessments of argumentation-particularly oral argumentation, as McNeill and Knight (2013) found that many teachers reported difficulty making sense of the quality of oral arguments during classroom discussions. Hence the need for more attempts to develop assessments of oral argumentation.…”
Section: Moving Forwardmentioning
confidence: 99%
“…But knowledge of content and knowledge of argument is not enough. Teachers have demonstrated various levels of proficiency with their pedagogical content knowledge of scientific argumentation, such as various levels of difficulty with analyzing classroom argumentation and/or choosing appropriate driving questions that promote authentic argumentation (McNeill & Knight, 2013). Hence, the development of a validated assessment of teacher pedagogical content knowledge (PCK) for argumentation by McNeill, serves as an asset to teacher professional development efforts moving forward.…”
Section: Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, para que a argumentação em aula seja significativa, uma série de 44 variáveis necessitam de ser tomadas em consideração, tais como os materiais usados, o tipo de tarefa e como é organizada, o objetivo do debate ser explícito, e por último, a preparação do professor para que tais atividades aconteçam de forma "plena" e sistemática. Este último fator só recentemente foi foco de investigação, seja como parte das condições criadas para que o discurso na aula se tornasse argumentativo (De Chiaro & Leitão, 2005), seja como requisito do desenvolvimento profissional (DP) dos professores (McNeill & Knight, 2013).…”
Section: Introductionunclassified
“…Contudo, para que a argumentação em aula seja significativa, uma série de 44 variáveis necessitam de ser tomadas em consideração, tais como os materiais usados, o tipo de tarefa e como é organizada, o objetivo do debate ser explícito, e por último, a preparação do professor para que tais atividades aconteçam de forma "plena" e sistemática. Este último fator só recentemente foi foco de investigação, seja como parte das condições criadas para que o discurso na aula se tornasse argumentativo (De Chiaro & Leitão, 2005), seja como requisito do desenvolvimento profissional (DP) dos professores (McNeill & Knight, 2013).A necessidade emergente de apoio aos professores na construção de atividades orientadas para a argumentacão é também evidente em Portugal, por duas razões principais. A primeira relaciona-se com o uso dos manuais, que continuam a ser incongruentes com as principais competências implicadas no PISA (Antunes & Galvão, 2015), em especial o requerimento de que sejam melhoradas as aptidões argumentativas dos estudantes (Almeida, Figueiredo, & Galvão, 2012).…”
unclassified